TMEM16A Inhibition Preserves Blood–Brain Barrier Integrity After Ischemic Stroke - Liu, Pin-yi; Zhang, Zhi; Liu, Yi; Tang, Xue-lian; Shu, Shu; Bao, Xin-yu; Zhang, Yan; Gu, Yue; Xu, Yun; Cao, Xiang (Frontiers in Cellular Neuroscience, 2019)
The inflammatory response plays a pivotal role in blood-brain barrier (BBB) destruction following ischemic brain injury. Enhanced leukocyte adhesion to vascular endothelial cells is an essential event in the inflammatory process. TMEM16A, a newly discovered protein regulating calcium-activated chloride channels, is widely expressed in eukaryotes. Recent studies have suggested that upregulated expression of TMEM16A is associated with the occurrence and development of many diseases. However, the role of TMEM16A in regulating BBB integrity after ischemic stroke has not been fully investigated. In this study, we found that TMEM16A is mainly expressed in brain endothelial cells and upregulated after ischemic stroke in the mouse brain. Caccinh-A01, an TMEM16A inhibitor that reduced its upregulation, attenuated brain infarct size and neurological deficits after ischemic stroke. ICAM-1 and MPO expression and BBB permeability were decreased after TMEM16A inhibitor administration. In addition, TMEM16A silencing rescued oxygen-glucose deprivation/reoxygenation (OGD/R)-induced transendothelial permeability in vitro accompanied by decreased ICAM-1 expression and leukocyte adhesion. Furthermore, our mechanistic study showed that TMEM16A knockdown alleviated NF-κB activation and nuclear translocation, indicating that TMEM16A knockdown downregulated OGD/R-induced ICAM-1 expression in an NF-κB-dependent manner. Finally, NF-κB inhibitor treatment also alleviated OGD/R-induced BBB permeability, confirming that activated NF-κB and increased ICAM-1 are essential factors involved in ischemia-induced BBB damage. Thus, our research provides a promising treatment strategy against BBB destruction after ischemic stroke, and TMEM16A may become a potential target for the treatment of ischemic stroke.